Primary synovial sarcoma of the uterus - Dundr, Pavel; Fischerová, Daniela; Povýšil, Ctibor; Tvrdík, Daniel; Cibula, David (Pathology oncology research, 2012)
We report a case of a 52-year-old female with synovial sarcoma of the uterine corpus. Grossly, the partly polypoid tumor involved the endometrium with invasion into the inner half of the myometrium. Histologically, the tumor showed biphasic structure with the predominance of poorly differentiated small to medium sized round to oval cells. These cells showed high nuclear to cytoplasmic ratio and were arranged in diffuse sheets. Other component consisted of larger epitheloid cells with ample eosinophilic cytoplasm arranged in irregular nests. These cells were only present in a small amount. Immunohistochemically, the tumor cells in both components showed the expression of EMA, S-100 protein, CD99, and NSE. RT-PCR analysis showed the presence of SYT-SSX1 fusion transcript. At present, the patient shows no signs of tumor relapse 56 months after the diagnosis. To the best of our knowledge, this is the first report of synovial sarcoma arising in uterus.
Keywords: sekundární malignity; Female; Sarcoma, Synovial; ženské pohlaví; fúzní onkogenní proteiny; lidé; Oncogene Proteins, Fusion; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; nádory děložního čípku; RNA, Messenger; imunoenzymatické techniky; Neoplasms, Second Primary; Reverse Transcriptase Polymerase Chain Reaction; Immunoenzyme Techniques; Uterine Cervical Neoplasms; lidé středního věku; synoviom; Middle Aged; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Humans